(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
The incidence of placenta accreta spectrum (PAS) disorders has increased over the last decades due to increase in cesarean deliveries, resulting in increase in cesarean hysterectomies , maternal mortality and morbidity but since last few years there has been a gradual shift towards the idea of conservative management. Conservative management of PAS is known to reduce major obstetric hemorrhage and salvage hysterectomy. We present a case of placenta accreta diagnosed by ultrasound where management of post-partum hemorrhage was accomplished by conservative surgery. The concise steps taken in management of placenta accreta before and during cesarean section were: Availability of 4 donors with cross match; Stark cesarean section; atraumatic clamps around uterine arteries; ureterotonic drugs; external (B-Lynch suture); and application of diathermy where required. This experience indicates that few selected cases of PAS could be managed conservatively who are at risk of intra-partum hemorrhage and post-partum hemorrhage.